Analysing The Rule of Common Law In Supervision Of Illegal Wild Trade Cites By Route Sea’s - Efendi, Yusuf; Wanto, Alfi Haris; Domai, Tjahjanulin (Institut Teknologi Sepuluh Nopember, 2024)
Indonesia is a maritime country with vast marine areas. Furthermore, Indonesia is also a country with the second-largest biodiversity in the world. Many endemic flora and fauna in Indonesia, some even endangered, are vulnerable to becoming illegal trade commodities, primarily through domestic and international sea routes. Therefore, endemic flora and fauna in Indonesia must be protected to prevent extinction. Customs is a community protector that monitors export activities through the law enforcement of CITES (Convention on International Trades on Endangered Species of Wild Flora and Fauna). This study aims to analyze the effectiveness of supervision carried out by Customs as a community protector in monitoring illegal wildlife exports through the prohibition and restriction supervision scheme at Tanjung Priok Port. The method used in this paper is qualitative research with a literature study approach. Based on the results of the data analysis that has been carried out, it can be concluded that customs have an essential role in the export of protected flora and fauna. For the supervision carried out by Customs to be effective and maximum, several steps are needed, including no collusion, computerization of services provided, and finally, implementing situational crime prevention against illegal wildlife trade.